2015
DOI: 10.3389/fncel.2015.00059
|View full text |Cite
|
Sign up to set email alerts
|

Control of the neurovascular coupling by nitric oxide-dependent regulation of astrocytic Ca2+ signaling

Abstract: Neuronal activity must be tightly coordinated with blood flow to keep proper brain function, which is achieved by a mechanism known as neurovascular coupling. Then, an increase in synaptic activity leads to a dilation of local parenchymal arterioles that matches the enhanced metabolic demand. Neurovascular coupling is orchestrated by astrocytes. These glial cells are located between neurons and the microvasculature, with the astrocytic endfeet ensheathing the vessels, which allows fine intercellular communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 103 publications
0
49
0
2
Order By: Relevance
“…This increase in blood flow provides the signal analyzed in functional MRI analyses (for review, see Hillman, 2014; Raichle and Mintun, 2006). The mechanisms underlying this neurovascular coupling have been the subject of intense scrutiny and several different signals have been implicated (for reviews, see Attwell et al, 2010; Figley and Stroman, 2011; Howarth, 2014; Iadecola and Nedergaard, 2007; Koehler et al, 2009; Munoz et al, 2015; Petzold and Murthy, 2011; Tran and Gordon, 2015). The signals and cells that mediate this response are likely different for arterioles and capillaries (Attwell et al, 2010; Hall et al, 2014).…”
Section: Glutamate Transport and The Neurovascular Responsementioning
confidence: 99%
“…This increase in blood flow provides the signal analyzed in functional MRI analyses (for review, see Hillman, 2014; Raichle and Mintun, 2006). The mechanisms underlying this neurovascular coupling have been the subject of intense scrutiny and several different signals have been implicated (for reviews, see Attwell et al, 2010; Figley and Stroman, 2011; Howarth, 2014; Iadecola and Nedergaard, 2007; Koehler et al, 2009; Munoz et al, 2015; Petzold and Murthy, 2011; Tran and Gordon, 2015). The signals and cells that mediate this response are likely different for arterioles and capillaries (Attwell et al, 2010; Hall et al, 2014).…”
Section: Glutamate Transport and The Neurovascular Responsementioning
confidence: 99%
“…On the other hand, controlled opening of hemichannels plays an important role in neurovascular coupling, a process to maintain brain function with proper blood flow. Based on experimental data, it is suggested that neurovascular coupling may activate nitric oxide production which leads to Ca 2+ influx through hemichannels leading to the propagation of the signal to end feet of astrocytes to enhance the neurovascular coupling as reviewed in (Munoz et al, 2015). Also, nitric oxide released by the astrocytic hemichannels at end feet may contribute to the vasodilation.…”
Section: Connexin Hemichannelsmentioning
confidence: 99%
“…During neurovascular coupling, vasoactive signals arising from activated neurons or astrocytes influence local vessel tone and thus regulate regional blood flow to match the energetic needs of neuronal function. 69 This regulatory process is thought to be a feed-forward signaling pathway, starting with increased neuronal activity and resulting in changes in arteriole diameter. 10 It is known that triggering astrocyte calcium transients results in vasoconstriction of neighboring arterioles.…”
mentioning
confidence: 99%